Listening Beyond the Classroom: Indonesian Student's Experience with the LearnEnglish Podcast - Umar, Vebrianti; Elsa Rosalina; Rahma Pitria Ningsih (General English Education, 2026)
In the digital era, listening skills can be acquired by utilizing LearnEnglish Podcast from the British Council, which provides a variety of free and paid online materials and courses for all ages and skill levels: applications, websites, podcasts, videos, and live classes. In this qualitative research with a narrative design, the researcher conducted observations and interviews with one English language education student recruited through purposive sampling. The research objective is to investigate participant's experiences using the LearnEnglish podcast to support listening skills acquisition. The results of the coding-based data analysis revealed four main findings. First, the LearnEnglish Podcast offered meaningful opportunities for listening practice. Second, the participant gained new vocabulary that supported better comprehension of spoken English. Third, the application was perceived as effective due to its comprehensive listening features, ease of use, flexibility, and free access. However, a key limitation concerned the need to download podcast files, which created difficulties related to limited mobile storage and the necessity for frequent deletion and re-downloading. There are two implications for the application and learners. The podcast should be shorter to suit limited storage. Learners should also use the LearnEnglish application flexibly and systematically to maximize its features for effective listening practice.